An Analysis of Graduate Theses on Academic Procrastination Published in Turkey Between 2003 and 2021 - Sarıaslan, Nurcan; Akbulut, Cansel Kadıoğlu (Bartın Üniversitesi, 2022)
The purpose of this study is to analyze the graduate theses on academic procrastination published in Turkey to evaluate their status in terms of various variables. For this purpose, a list of the theses was obtained as a result of a search in the National Thesis Center using the keywords “academic procrastination” in both Turkish and English languages. From the list, all the open-access theses of which sample consisted of students were included in the study. In line with the determined criteria, a total of 101 graduate theses published between 2003 and 2021 were analyzed through document analysis based on the descriptive content analysis method. The distribution of the theses was examined based on variables including the program type, year of publication, the university, institute, and department where the study was conducted, language, gender of the researcher, research design, sampling method, sample size, region of the data collection, level of education and the data collection tool used to measure academic procrastination. The study revealed that the theses were mostly written in the master's program (86.14%), in 2019 (15.84%), at Gazi University (5.94%), in the Institute of Educational Sciences (56.44%), in the Department of Educational Sciences (53.47%), in the Turkish language (92.08%), by female researchers (59.41%), based on survey design (94.06%), using random sampling (59.41%), with a sample size of 400-499 (22.77%), with data collected from Central Anatolia (28.71%) from undergraduate students (53.46%) using the Academic Procrastination Scale (56.43%) developed by Çakıcı (2003).

Bu çalışmanın amacı akademik erteleme üzerine Türkiye'de yayımlanmış lisansüstü tezlerin çeşitli değişkenler açısından durumunu değerlendirmeye yönelik analizini yapmaktır. Bu amaç doğrultusunda Ulusal Tez Merkezi'nde “akademik erteleme” ve İngilizcesi olan “academic procrastination” anahtar kelimeleri kullanılarak yapılan tarama sonucunda bulunan lisansüstü tezlerinin bir listesi çıkarılmıştır. Bu tezler arasından çalışma grubunu öğrencilerin oluşturduğu ve erişim izni bulunan tüm lisansüstü tezler araştırmaya dahil edilmiştir. Belirlenen ölçütler doğrultusunda 2003-2021 yılları arasında yayımlanan toplam 101 lisansüstü tez, betimsel içerik analizi yöntemine dayalı doküman analizi yapılarak incelenmiştir. Çalışmada incelenen tezler program türü, basıldığı yıl, araştırmanın yapıldığı üniversite, enstitü ve anabilim dalı, yazıldığı dil, araştırmacının cinsiyeti, araştırma deseni, örneklem belirleme yöntemi, örneklem büyüklüğü, veri toplanan bölge, öğrenim kademesi ve akademik ertelemeyi ölçmek için kullanan veri toplama aracı değişkenlerine göre dağılımı incelenmiştir. Çalışma sonucunda incelenen tezlerin ağırlıklı olarak yüksek lisans programında (%86.14), 2019 yılında (%15.84), Gazi Üniversitesinde (%5.94), Eğitim Bilimleri Enstitüsünde (%56,44), Eğitim Bilimleri Anabilim Dalında (%53,47), Türkçe dilinde (%92,08), kadın araştırmacılar tarafından (%59,41), tarama desenine dayalı (%94,06), seçkisiz örnekleme yöntemi kullanılarak (% 59,41), 400-499 arasında örneklem büyüklüğü ile (%22,77), İç Anadolu Bölgesinde (28.71%), lisans öğrencileri ile (%53,46) ve Çakıcı (2003) tarafından geliştirilen Akademik Erteleme Ölçeği (%56,43) kullanılarak yapıldığı tespit edilmiştir.
Türkiye'de Akademik Erteleme Üzerine 2003-2021 Yılları Arasında Yapılan Lisansüstü Tezlerin Analizi
Keywords: Other Fields of Education; Alan Eğitimleri